Incidence of airborne fungal spores in the air of hill top - Mishra2; K.V. Badar3, K. Sharma1*, M. Agrawal1, Mohit S. (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Aeromycoflora of Dongargarh was studied with the help of Petriplate method. Total 389 fungal colonies represented 31 fungal types were observed during the present investigation period. Out of 31 fungal types, Maximum numbers of fungi (24) were isolated from anamorphic group, (03) from Ascomycotina and Mycelia sterilia and minimum (01) from Zygomycotina The fungal species were Cladosporium oxysporium, Fusarium Mycelia sterilia, Aspergillus, Penicillium, Curvularia, Cladosporium, Rhizopus ,Trichoderma species were observed. It is found that maximum percentage contribution is observed for Cladosporium oxysporium (26.73) Aspergillus niger (15.16), A. versicolor (9.51), followed by A. fumigatus (6.68). On the contrary, minimum percentage contribution (0.25) is observed for Aspergillus terreus.